How the WAP stabilized and rationalized the exchanges on the Senegalese markets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
There was once a time when the wholesalers called all the shots on the markets of Dakar by forcing the prices down as low as was possible.